"A Library of Photographs Covering the Entire Continent": Walkabout Magazine and the Politics of Documentary in Post-War Australia. (2nd January 2020) - Magagnoli, Paolo
Abstract: Spanning five central decades of the mid-twentieth century (1934–1974), Walkabout was one of Australia's best-loved illustrated weeklies. Photography played a crucial role in the magazine's attempt to represent the vast Australian continent and its neighboring countries. While historians and critics have regarded the magazine as an example of boosterish nationalism and middle-brow anti-intellectualism, I argue that the periodical should be considered as an amalgam of reactionary and progressive ideals: Walkabout was a paradoxical combination of high-modernism and romantic anti-capitalism, conservative nationalism and left populism. Although it glossed over many of the problems facing the country, the editors' emphasis on "factual photography" was indicative of a democratic impulse. I offer an examination of the magazine's coverage of extractive projects as an example of Walkabout 's ideological contradictions. In particular, I look at Laurence Le Guay and Robert Emerson Curtis's 1947 photo-essay about the mining town of Mount Isa to show how the periodical attempted to reconcile two antagonistic gazes: that of the corporate engineer and that of the miner.